Methods for the economic evaluation of health care programmes - Michael F. Drummond (Oxford University Press, 2005)
This new edition builds on the strengths of previous editions being clearly written in a style accessible to a wide readership. Key methodological principles are outlined using a critical appraisal checklist that can be applied to any published study. The methodological features of the basic forms of analysis are then explained in more detail with special emphasis of the latest views on productivity costs, the characterization of uncertainty and the concept of net benefit. The book has been greatly revised and expanded especially concerning analyzing patient-level data and decision-analytic modeling. There is discussion of new methodological approaches, including cost effectiveness acceptability curves, net benefit regression, probalistic sensitivity analysis and value of information analysis